The Errors in the Use of EYD in Research Paper Writing by Third-Semester Students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Universitas Flores - Djumadin, Hawiah; Bunga, Rosa Dalima (The Future of Education Journal, 2025)
The research question in this study is: What are the types of errors in the use of the Enhanced Spelling System of the Indonesian Language (EYD) found in the papers written by third-semester students of the Literary Ecocriticism course, Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Universitas Flores, in the 2022/2023 academic year? This study aims to identify the types of EYD usage errors in the papers written by third-semester students of the Literary Ecocriticism course in the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Universitas Flores, in the 2022/2023 academic year. The approach used in this research is a qualitative approach. The data in this study are presented in words or sentences. The method employed is literature study. Data collection techniques include reading, note-taking, and underlining. Theories used in this study are error analysis theory and writing skills theory. The results of the study show that there are three types of EYD usage errors in the students’ papers: (1) errors in the use of capital letters; (2) word usage errors, including base words, verbs, nouns, adjectives, prepositions, pronouns, adverbs, and numerals; and (3) punctuation errors, including the use of periods, commas, double quotation marks, single quotation marks, colons, and hyphens.